Science and Technology Growth in Universities of Brazil after the Creation and Implementation of Innovation Law | Crecimiento de la Ciencia y Tecnología en las universidades de Brasil después de la creación e implementación de la Ley de Innovación - Neres-Menezes, Edmara Menezes Thays; Andrade-Santos, Rosa Elaine; Francisco-da-Silva, Gabriel; Leitão-Russo, Suzana (Razón y Palabra., 2016)
With changing economic paradigms, Brazil has felt the need to establish public policies to strengthen science and technology, then expanded the number of teachers in higher education institutions and were created legal mechanisms in order to consolidate innovation in the country. The objective was to conduct an analysis of scientific and technological development indicators in Brazil, noting that the new investment policy and the expansion of doctors in universities has influence on increasing the production technology of the country. Expansion of doctors investigators in the 2006 to 2014 IES has an increase of almost 70% was found. In production technology, makes a comparison between 2004 where the production technology reached the amount of 12,014 that compared to the data of 2014 it is noted an increase of almost 200% checking positives after the creation of the Innovation Law. After statistical analysis the increase in the number of doctors accounted for 98% increase in production technology, proving how strong this relationship. <span title="With changing economic paradigms, Brazil has felt the need to establish public policies to strengthen science and technology, then expanded the number of teachers in higher education institutions and were created legal mechanisms in order to consolidate innovation in the country.">Con los paradigmas económicos cambiantes, Brasil ha sentido la necesidad de establecer políticas públicas para fortalecer la ciencia y la tecnología, luego amplió el número de docentes en instituciones de educación superior y se crearon mecanismos legales para consolidar la innovación en el país. <span title="The objective was to conduct an analysis of scientific and technological development indicators in Brazil, noting that the new investment policy and the expansion of doctors in universities has influence on increasing the production technology of the country.">El objetivo fue realizar un análisis de indicadores de desarrollo científico y tecnológico en Brasil, señalando que la nueva política de inversión y la expansión de los médicos en las universidades influye en el incremento de la tecnología de producción del país. La expansión de los investigadores médicos en el 2006 a 2014 IES tiene un aumento de casi el 70% se encontró. <span title="In production technology, makes a comparison between 2004 where the production technology reached the amount of 12,014 that compared to the data of 2014 it is noted an increase of almost 200% checking positives after the creation of the Innovation Law.">En tecnología de producción, hace una comparación entre 2004 donde la tecnología de producción llegó a la cantidad de 12.014 que comparado con los datos de 2014 se nota un aumento de casi 200% comprobando positivos después de la creación de la Ley de Innovación. Después de un análisis estadístico, el aumento en el número de médicos representó un aumento del 98% en la tecnología de producción, demostrando cuán fuerte es esta relación.